Offshore aquaculture: Spatial planning principles for sustainable development. Issue 2 (24th December 2016) - Gentry, Rebecca R.; Lester, Sarah E.; Kappel, Carrie V.; White, Crow; Bell, Tom W.; Stevens, Joel; Gaines, Steven D.
Abstract: Marine aquaculture is expanding into deeper offshore environments in response to growing consumer demand for seafood, improved technology, and limited potential to increase wild fisheries catches. Sustainable development of aquaculture will require quantification and minimization of its impacts on other ocean‐based activities and the environment through scientifically informed spatial planning. However, the scientific literature currently provides limited direct guidance for such planning. Here, we employ an ecological lens and synthesize a broad multidisciplinary literature to provide insight into the interactions between offshore aquaculture and the surrounding environment across a spectrum of spatial scales. While important information gaps remain, we find that there is sufficient research for informed decisions about the effects of aquaculture siting to achieve a sustainable offshore aquaculture industry that complements other uses of the marine environment. Abstract : As marine aquaculture expands into new offshore environments, diverse ecological considerations across a spectrum of spatial scales will be necessary to ensure sustainable outcomes. Using an ecological lens, we synthesize a broad multidisciplinary literature and provide recommendations for incorporating spatially explicit ecological and socioeconomic interactions into spatial planning for offshore aquaculture development.